Zamknięcie Kunstanii - Sztaba, Wojciech (Przestrzenie Teorii, 2019)
The Closing of Kunstania is a short tale about art that has been hidden away from its audience in a garden behind high walls. In this refuge, there are neither audio-guides nor art education nor interactive apps. Kunstania reminds us of another possibility to encounter art without mediators, without an aura of masterpieces, and without the promise of an extraordinary event. Instead, a way through a labyrinth of rooms and corridors, where, perhaps, things and tales are stored, but must be found on your own, wandering, returning and recollecting.